Gender influence on the adaptation of atrial performance to training. Issue 6 (3rd July 2017) - Sanchis, Laura; Sanz-de La Garza, Maria; Bijnens, Bart; Giraldeau, Genevieve; Grazioli, Gonzalo; Marin, Josefa; Gabrielli, Luigi; Montserrat, Silvia; Sitges, Marta
Abstract: Background: High-intensity training has been associated with atrial remodelling and arrhythmias in men. Our purpose was to analyse atrial performance in female endurance athletes, compared to male athletes and controls. Methods: This was a cross-sectional study. We included four groups: female athletes, females controls, male athletes and male controls. Left (LA) and right atrial (RA) volumes and function were assessed using 2D and speckle-tracking echocardiography to determine peak atrial strain-rate at atrial (SRa) and ventricular contraction (SRs), as surrogates of atrial contractile and reservoir function, respectively. ANOVA and Bonferroni's statistical tests were used to compare variables among groups. Results: We included 82 subjects, 39 women (19 endurance athletes, 20 controls) and 43 men (22 endurance athletes, 21 controls). Mean age was similar between groups (36.6 ± 5.6 years). Athletes had larger bi-atrial volumes, compared to controls (women, LA 27.1 vs. 15.8 ml/m 2, p  < 0.001; RA 22.31 vs. 14.2 ml/m 2, p  = 0.009; men, LA: 25.0 vs. 18.5 ml/m 2, p  = 0.003; RA 30.8 vs. 21.9 ml/m 2, p  < 0.001) and lower strain-rate (women, LASRa −1.60 vs. −2.18 s −1, p  < 0.001; RASRa −1.89 vs. −2.38 s −1, p  = 0.009; men, LASRa −1.21 vs. −1.44 s −1, p  = 1; RASRa −1.44 vs. −1.60 s −1, p  = 1). However, RA indexed size was lower and bi-atrial deformation greater in female athletes, compared to male athletes. Conclusions: The atria of both male and female athletes shows specific remodelling, compared to sedentary subjects, with larger size and less deformation at rest, particularly for the RA. Despite a similar extent of remodelling, the pattern in women had greater bi-atrial myocardial deformation and smaller RA size.